الحماية القانونية للحرية الدينية لمسلمي بورما - أكرور، ميريام Akrour, Miriam; بن رجدال، آمال Bin Rajdal, Amal (جامعة الجزائر1 بن يوسف بن خدة, 2021)
تعد حرية الدين من الحريات الأساسية المحمية بقواعد القانون الدولي، كما هي مكرسة بموجب القوانين الداخلية للدول، التي تتجه بعضها إلى تأطيرها بشكل يؤدي إلى حد التضييق عند ممارسة الشعائر الدينية بالنسبة للأقليات التي تتبع بعض الديانات، حيث يتم اضطهادهم وحرمانهم من ممارسة دياناتهم، تلك هي المعاناة التي تعيشها يوميا الأقلية المسلمة في ميانمار، رغم وجود آليات تكفل حرية المعتقد في المواثيق الدولية من جهة وذلك من خلال النصوص العامة لحقوق وحريات الإنسان أو النصوص الخاصة التي تهدف إلى القضاء على أشكال التمييز ومن جهة أخرى حماية المعتقد بموجب القانون الداخلي لجمهورية بورما التي تزعم أنها لا تعتمد أي دين رسمي، وتدعي حماية الحرية الدينية في حين أنها تعامل الذين يدينون بالبوذية معاملة تمييزية مع إقصاء واضطهاد لأقلية الروهينقا المسلمة.
Freedom of religion is considered one of the basic freedoms, protected by the rules of international law. as it is devoted under the internal laws of states, some of which tend to frame it in a manner that leads to a level of constraint when practicing religious rites for minorities that follow some religions, where they are persecuted and deprived of practicing their religions, those are The suffering suffered daily by the Muslim minority in Myanmar, despite the existence of mechanisms that guarantee freedom of belief in international conventions on the one hand, through general texts of human rights and freedoms or special texts that aim to eliminate discrimination and on the other hand protect the belief under the internal law of the Republic of Burma, which claims It does not adopt any official religion, and claims to protect religious freedom while treating those who condemn Buddhism with a discriminatory treatment with exclusion and persecution of the Muslim Rohingya minority.
Keywords: الأقليات المسلمة -- الاضطهاد الديني -- حقوق الإنسان -- القانون الدولي